Predatory and energetic relations of woodpeckers to the Engelmann spruce beetle - Koplin, James Ray, author; Baldwin, Paul H., advisor; Steinhoff, Harold W., committee member; Pettus, David, 1925-2014, committee member; Wygant, Noel D., 1908-, committee member (Colorado State University. Libraries, 1967)
A general theory of the population dynamics of predator-prey systems was developed from a survey of pertinent literature. According to the theory, populations of simplified predator-prey systems fluctuate wildly and periodically. Complicating factors dampen the amplitude of the population fluctuations and thus exert a stabilizing influence on the systems. The predator-prey system between the Northern Three-toed, Hairy and Downy Woodpeckers, and the Engelmann spruce beetle was chosen for an investigation of the population dynamics of a natural predator-prey system. The population densities of several species of bark beetles attracted to trees killed and damaged by a fire on the study area in Northern Colorado, increased to levels that attracted the feeding attention of the woodpeckers. The numerical response of the woodpeckers to prey density was graded, that of the Northern Three-toed Woodpecker was the most pronounced and that of the Downy Woodpecker was the least pronounced. Spatial and temporal differences were noted in the foraging behavior of the three species of woodpeckers; similar but less apparent differences were also noted in the foraging behavior between the sexes of the Northern Three-toed and Hairy Woodpeckers. Both the interspecific and intersexual differences in foraging behavior were correlated with morphological and dietary differences. The metabolic demands of free-living woodpeckers were estimated by feeding diets of known caloric content to active woodpeckers in cages at several different ambient temperatures. Estimates were also made of the caloric content of Engelmann spruce beetle larvae and the rate at which they are digested by the woodpeckers. Combining these estimates with the estimates of the relative densities of woodpeckers, and the average number of spruce beetle larvae found per woodpecker stomach made it possible to calculate the number of larvae consumed by each species of woodpecker. This method gave results very similar to the usual method whereby the number of larvae surviving in bark protected from woodpeckers is compared with the number surviving in bark exposed to woodpeckers. Every aspect of the predator-prey system between woodpeckers and the Engelmann spruce beetle, except the number of larvae destroyed, conforms to general theory. The number of prey destroyed in this predator-prey system is higher than that known for any other system between vertebrate predators and invertebrate prey.
Keywords: White pine weevil; Woodpeckers